Dante's bones how a poet invented Italy - Raffa, Guy P. (The Belknap Press of Harvard University Press, 2020)
Like a saint's relics, Dante's bones have been stolen, exhumed, and worshiped. Guy Raffa narrates the Florentine poet's hereafter--the physical afterlife of the writer who vividly imagined the spiritual afterlife. In the story of the bones lies the tale of Dante's evolution from Renaissance to Italian to nationalist hero, and finally global icon